Preliminary Study of Swiftlet House Transition for the Cultivation of Grey Oyster Mushrooms - Hidayat, Muhammad Fariz; Novita, Aisar; Khulidin, Khairul Asfamawi; Ahmad, Kamarul Zaman; Akhir, Nurasmaliza Mohd; Fazil, Nurhidayah; Shahbuddin, Mohd Afif; Halim, Nur Hafizoh; Khair, Hadriman (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University, 2023)
The transformation of the nest swiftlet house for the cultivation of grey oyster mushrooms is seen as a strategic transition. A few improvements and a little expense given a good value of impact on yield (mushrooms). A total of 119.3 g per bag of grey oyster media produced in the swiftlet house, Sg. Petani, Kedah compared to 149.1 g per media bag in the Environmental Controlled Mushroom House (CEMH), MARDI Headquater, Serdang, Selangor. Although, mushroom yield is higher (CEMH) than swiftlet house but CEMH operating cost is bigger (high electricity consumption). However, there was no significant difference in the yield of mushrooms in the swiftlet house (119.3 g per media bag) with the DANA project mushroom house, MARDI Kedah Office, Alor Setar, Kedah (115.9 g per media bag). Indirectly, giving an entrepreneur a second chance against financial loss.